Analisis Hukum Perdata Terkait Pertanggungjawaban Pengangkut dalam Angkutan Umum Bus di Indonesia - Milafebina, Rachel; Syailendra, Moody Rizqy (Peneliti.net, 2024)
Indonesia, as an archipelagic country with a large territory and population spread across various islands, relies heavily on an efficient transportation system to connect regions and increase population mobility. One of the modes of transportation most widely used by the public is public bus transportation, both for inter-city and intra-city transportation. One of them is the Sinar Jaya Group. Normative legal research methods are methods that focus on applicable legal norms, as well as the legal principles that underlie them. Objective: Learn how civil law regulates the liability of carriers in emergency situations, such as accidents or unforeseen events. Results of writing Bus carriers have a responsibility regulated in the Road Traffic and Transportation Law to deliver passengers safely to their destination. If an accident occurs, the carrier is obliged to provide compensation to passengers who experience losses.